THE DIGITAL CLOUD AS A REQUIREMENT FOR ESTABLISHING THE FOUNDATIONS OF THE DIGITAL ECONOMY AMID CONTEMPORARY TECHNOLOGICAL CHALLENGES - REFERENCE TO SERVICE MODELS IN ITS APPLICATIONS - Menasri, Dr. yahia; Ilimi , Dr. Chihab; Mohamed, Trifa (The journal of contemporary issues in business and government, 2024)
The transition towards a digital economy constitutes a cornerstone in contemporary technological evolution, highlighting the role of the digital cloud as a crucial factor and catalyst for growth and innovation. The digital cloud, with its flexibility, speed, and efficiency in data storage and processing, offers new opportunities for both institutions and individuals to adapt to ongoing technological challenges. It provides effective solutions to these challenges through a flexible and secure infrastructure capable of handling and analyzing vast amounts of data efficiently. This investigation seeks to illuminate the critical role of cloud computing in laying the groundwork for the digital economy, demonstrating how cloud technology enhances operational efficiencies and augments adaptability for businesses within the digital commerce landscape. Cloud computing has emerged as the preeminent technology among information society professionals and workers, embodying a collection of services delivered by providers through the internet. This enables customers to tap into the providers’ advanced capabilities and resources without the necessity of investing in costly infrastructure to achieve similar functionalities within their organizations.